From cloning animals to cloning man? - Di Pietro, Maria Luisa (Medicina e Morale, 1997)
The news that some English researchers were able to produce the sheep "Dolly" by cloning the genetic patrimony of an adult sheep, provoked a series of reactions in the public opinion regarding the fear that the experiment might be repeated on man too. Consequently debates were organized, both in parliaments and in commissions created ad hoc, and national and international directives were issued. But is the dreaded cloning of human individuals ethically acceptable or not? And what would be the anthropological significance of this operation? After a brief introduction on the scientific aspects of cloning and the justifications proposed in its favour, not only for cloning animals but also human beings, the author analyses the criteria that have been used in the documents of the various institutions in order to provide a moral judgement on this practice: from "contractualism" to "consequentialism" to a so-called "overall evaluation".